The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1103/physrevlett.102.196403
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Charge Frustration in the Molecular Conductor(DIDCNQI)2Ag

Abstract: We theoretically study the effect of spiral-type charge frustration in a quasi-one-dimensional molecular conductor (DI-DCNQI)2Ag. We clarify how the spiral frustration in the interchain Coulomb repulsion is relieved and leads to a self-organization of complex charge-lattice ordered chains, in agreement with the recent synchrotron x-ray study [T. Kakiuchi, Phys. Rev. Lett. 98, 066402 (2007)10.1103/PhysRevLett.98.066402]. In addition, we find that a keen competition between charge and lattice degrees of freedom … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…34,35) A difference between our model and the situation in the actual TMTTF compounds is that, the present calculation does not include the intrinsic lattice dimerization along the chains while it exists in the materials, which leads to another non-linear term in the bosonized Hamiltonian. 22) In (DI-DCNQI) 2 Ag, even though recent studies 36,37) revealed that the system undergoes a more complex chargelattice ordering than the simple CO we investigate in this paper, the T dependence in ρ(T ) across T = T CO observed at high pressure resembles our calculated data, whereas the kink at T = T CO is smeared out at ambient pressure. 38,39) All these Q1D molecular conductors show no anomaly in the bulk χ σ (T ) at T = T CO , while NMR measurements show the appearance of atomic sites showing different Knight shifts and relaxation rates: 40,41) these are also consistent with our analysis.…”
Section: Summary and Discussionsupporting
confidence: 68%
“…34,35) A difference between our model and the situation in the actual TMTTF compounds is that, the present calculation does not include the intrinsic lattice dimerization along the chains while it exists in the materials, which leads to another non-linear term in the bosonized Hamiltonian. 22) In (DI-DCNQI) 2 Ag, even though recent studies 36,37) revealed that the system undergoes a more complex chargelattice ordering than the simple CO we investigate in this paper, the T dependence in ρ(T ) across T = T CO observed at high pressure resembles our calculated data, whereas the kink at T = T CO is smeared out at ambient pressure. 38,39) All these Q1D molecular conductors show no anomaly in the bulk χ σ (T ) at T = T CO , while NMR measurements show the appearance of atomic sites showing different Knight shifts and relaxation rates: 40,41) these are also consistent with our analysis.…”
Section: Summary and Discussionsupporting
confidence: 68%
“…In parallel to, and independent of this theoretical indication, CO was observed by NMR [30] in another quasi-one-dimensional CT, (DI-DCNQI) 2 Ag (DI-DCNQI =2,5-diiodo-N,N'-Dicyanobenzoquinonediimine2,5-diiodo-N,N'-Dicyanobenzoquinonediimine), which is without dimerization at high temperatures. (Once CO sets in, a particular type of dimerization is stabilized [31,32].) A little later CO was also identified by NMR in an experiment with (TMTTF) 2 X (X = PF 6 and AsF 6 ) with finite dimerization [33].…”
Section: (Tmtcf) 2 Xmentioning
confidence: 95%
“…However, it is rather rare to have such an example in the existing compounds; Many have intrinsic dimerization and/or complex interchain coupling. DI-DCNQI 2 Ag [34,50] was formally considered to be the typical system, while recently it has been proposed that the ordered phase below T < 220 K might be a complex CO, DM mixed state [51,52]. TMTTF 2 X [35,53,54] family have been providing an ideal stage for such comparison, for systems with dimerization from the outset.…”
Section: Discussionmentioning
confidence: 99%